El Culto K en la era contemporánea: Crónica, génesis y apoteosis del proceso Kirchnerista - Korstanje, Maximiliano E. (Nómadas. Critical Journal of Social and Juridical Science, 2011)
Since 2003, the presidency of N. Kirchner and his wife Cristina F. de Kirchner in Argentina has given to society a reason to believe in the politics but at a higher risk. The initial trauma that subjugated the country during 2001 representing higher rates of poverty and unemployment has certainly paved the pathways for the advent of a new cult. As the previous argument given, the politic fear, dogmatism, suffering, greatness, word, sacred-text, victory, weakness, strength, and salvation are some of the most important indicators of the K-cult. From this perspective, this paper explores the similarities and differences with other religious fundamentalisms where the magical thinking not only predominates but also disconnects public opinion from the principle of reality. In doing so, the State elaborates a discourse as well as a much broader and complex process where negation, victimization and des-humanization converge.